2022
DOI: 10.1038/s41598-022-22815-8
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress decreases seed yield and postpones growth process of canola (Brassica napus L.) by changing nitrogen and carbon characters

Abstract: Salt stress is a major challenge for plant growth and yield achievement in canola (Brassica napus L.). Nitrogen (N) is considered as an essential nutrient involved in many physiological processes, and carbon (C) is the most component of plant biomass. N and C assimilations of canola plants are always inhibited by salt stress. However, the knowledge of how salt stress affects biomass and seed yield through changing N and C characters is limited. A field experiment was conducted to investigate the growth process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In addition, our study observed a decrease in the biomass of different organs at the seedling, flowering, and maturity stages when soil salinity increased. Our previous studies demonstrated that leaf photosynthesis at the seedling and flowering stage was inhibited under salt stress [ 29 , 30 ], leading to a reduction in biomass accumulation. Our findings differed from those of Bakirv et al, who reported that, compared to the non-NaCl condition, the treatment of 100 mM NaCl L −1 showed positive effects on the fresh weight and biomass production in some salt-tolerant varieties [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our study observed a decrease in the biomass of different organs at the seedling, flowering, and maturity stages when soil salinity increased. Our previous studies demonstrated that leaf photosynthesis at the seedling and flowering stage was inhibited under salt stress [ 29 , 30 ], leading to a reduction in biomass accumulation. Our findings differed from those of Bakirv et al, who reported that, compared to the non-NaCl condition, the treatment of 100 mM NaCl L −1 showed positive effects on the fresh weight and biomass production in some salt-tolerant varieties [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hurtado et al also reported that the treatment of 100 mM NaCl L −1 decreased C/N by 25% in sorghum plants and 17% in sunflower plants compared to the control [ 44 ]. Our previous field study also observed that C/N in the high-salt soil decreased compared to low-salt soil, indicating that salt stress disrupted the balance of C and N assimilation [ 30 ]. Generally speaking, the C and N assimilation was inhibited by salt stress, more so in C assimilation.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have found that salt stress affects plant uptake and assimilation of nitrogen by affecting nitrogen metabolism enzyme activities [ 12 , 13 ]. Carbon is also an important component of plant biomass [ 45 ], and SS mainly regulates starch synthesis as well as sucrose degradation processes, affecting the carbohydrate level of plants [ 46 ]. In this study, we found that the activities of NR, GS, and SS were significantly reduced in tobacco seedlings under salt stress, which also indicated that salt stress inhibited the activities of enzymes related to carbon and nitrogen processes, and reduced nitrogen uptake and utilization as well as carbohydrate synthesis in tobacco seedlings, which is in agreement with the results of previous studies [ 13 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, salt stress frequently occurs around the world. Although rapeseed is considered a moderate salt-tolerant crop, its physiological and biochemical processes are disrupted under a heavy saline environment ( Wang et al., 2022 ). In this study, we found that salt stress inhibited rapeseed seedling growth and photosynthesis while increasing Na content, ROS accumulation, and product of cell membrane lipid peroxidation as well as improved the antioxidants and accumulation of osmotic substances.…”
Section: Discussionmentioning
confidence: 99%